Use of Small Bowel Ultrasound to Predict Response to Infliximab Induction in Pediatric Crohn's Disease. Issue 5 (May 2021) - Dolinger, Michael T.; Choi, Jungwhan J.; Phan, Becky L.; Rosenberg, Henrietta K.; Rowland, John; Dubinsky, Marla C.
Abstract : Goal: The goal of this study was to explore the utility of small bowel ultrasound (SBUS) as a noninvasive tool to assess induction response to infliximab (IFX) in pediatric Crohn's disease (CD). Background: Inflammatory bowel disease management has shifted to a treat-to-target and tight control strategy utilizing noninvasive serum and fecal markers to monitor disease activity in response to therapy. Bowel wall changes as seen on cross-sectional imaging may be a more accurate marker of treatment success. Materials and Methods: Pediatric patients with CD with small bowel involvement initiating IFX were prospectively enrolled. Clinical activity, biomarkers, and SBUS findings were evaluated at baseline (T0) and postinduction at week 14 (T1). The primary outcome was to describe the changes in SBUS parameters pre and post IFX induction and how they associate with clinical and biomarker response. Descriptive statistics summarized the data and univariate analysis tested associations. Results: All 13 CD patients achieved steroid-free clinical remission ( P <0.001) and a decrease in C-reactive protein ( P =0.01) postinduction. Bowel wall hyperemia (BWH) ( P =0.01) and bowel segment length involved ( P =0.07) decreased postinduction. Decrease in fecal calprotectin at T1 moderately correlated with a decrease in bowel segment length ( r =0.57; P =0.04). No correlation was seen with a change in bowel wall thickness or BWH postinduction. Conclusions: Our pilot study suggests that SBUS is a feasible, noninvasive tool to measure early treatment response to IFX. BWH, not bowel wall thickness, is the first parameter to change. Larger longitudinal studies are warranted to validate the utility of SBUS as part of a disease monitoring strategy.